Cultural Models of the Coast in Australia: Toward Sustainability - Stocker, Laura; Kennedy, Deborah (Taylor & Francis, 2009)
Cultural models of the coast affect—and are affected by—our marine ethics, frameworks for coastal ownership, and management practices. The coast can be seen as an ecosystem with intrinsic values, a commodity that can be bought and sold, a community place where people meet, a landscape with aesthetic appeal, a productive system that generates profits, a property to be managed, or a spiritual realm that relates to proper order and reverence. Each of these cultural constructions interacts with the others and this can create conflicts over rights and responsibilities. Each construction has implications for who should manage the coast, to what ends, and by what means. This article explores the negative and positive implications of seven cultural models to the Australian coast and makes suggestions about the value of Australian Indigenous and sustainability perspectives to a durable human relationship with the coast. Examples are drawn from recent coastal developments in Australia, such as Native Title debates, the marine protected area process, and Coastcare.